A Neutralizing IL-11 Antibody Improves Renal Function and Increases Lifespan in a Mouse Model of Alport Syndrome. Issue 4 (April 2022) - Widjaja, Anissa A.; Shekeran, Shamini G.; Adami, Eleonora; Ting, Joyce G Wei; Tan, Jessie; Viswanathan, Sivakumar; Lim, Sze Yun; Tan, Puay Hoon; Hübner, Norbert; Coffman, Thomas; Cook, Stuart A.
Significance Statement: Alport syndrome (AS), a genetic disorder of the glomerular basement membrane, frequently leads to end stage renal failure. In an animal model of AS—mice lacking the Col4a3 gene, —angiotensin-converting enzyme inhibition is protective. The authors show that IL-11 is upregulated in the renal tubular epithelia of Col4a3 −/− mice; the IL-11 receptor (IL11RA1), expressed on podocytes and tubule cells, is upregulated in the diseased kidneys of Col4a3 −/− mice. Giving 6-week-old Col4a3 −/− mice a neutralizing IL-11 antibody (X203) reduced pathologic ERK and STAT3 activation and limited epithelial-to-mesenchymal transition; reduced kidney fibrosis, inflammation, and tubule damage; and improved kidney function. The median lifespan of Col4a3 −/− mice was prolonged 22% by ramipril alone, 44% with X203 alone, and 99% with ramipril+X203. These data suggest that anti-IL-11 therapies hold promise for treating kidney disease in AS. Visual Abstract: Abstract : Background: Alport syndrome is a genetic disorder characterized by a defective glomerular basement membrane, tubulointerstitial fibrosis, inflammation, and progressive renal failure. IL-11 was recently implicated in fibrotic kidney disease, but its role in Alport syndrome is unknown. Methods: We determined IL-11 expression by molecular analyses and in an Alport syndrome mouse model. We assessed the effects of a neutralizing IL-11 antibody (×203) versus an IgG control in Col4a3 −/− mice (lacking the gene encoding a type IV collagen component) on renal tubule damage, function, fibrosis, and inflammation. Effects of ×203, the IgG control, an angiotensin-converting enzyme (ACE) inhibitor (ramipril), or ramipril+X203 on lifespan were also studied. Results: In Col4a3 −/− mice, as kidney failure advanced, renal IL-11 levels increased, and IL-11 expression localized to tubular epithelial cells. The IL-11 receptor (IL-11RA1) is expressed in tubular epithelial cells and podocytes and is upregulated in tubular epithelial cells of Col4a3 −/− mice. Administration of ×203 reduced albuminuria, improved renal function, and preserved podocyte numbers and levels of key podocyte proteins that are reduced in Col4a3 −/− mice; these effects were accompanied by reduced fibrosis and inflammation, attenuation of epithelial-to-mesenchymal transition, and increased expression of regenerative markers. X203 attenuated pathogenic ERK and STAT3 pathways, which were activated in Col4a3 −/− mice. The median lifespan of Col4a3 −/− mice was prolonged 22% by ramipril, 44% with ×203, and 99% with ramipril+X203. Conclusions: In an Alport syndrome mouse model, renal IL-11 is upregulated, and neutralization of IL-11 reduces epithelial-to-mesenchymal transition, fibrosis, and inflammation while improving renal function. Anti-IL-11 combined with ACE inhibition synergistically extends lifespan. This suggests that a therapeutic approach targeting IL-11 holds promise for progressive kidney disease in Alport syndrome.